Ab Initio Density Functional Calculations and Infra-Red Study of CO Interaction with Pd Atoms on θ-Al2O3 (010) Surface - Chaitanya K. Narula (Nature Portfolio, 2017)
Abstract The ab initio density functional theoretical studies show that energetics favor CO oxidation on single Pd atoms supported on θ-alumina. The diffuse reflectance infra-red spectroscopy (DRIFTS) results show that carbonates are formed as intermediates when single supported Pd atoms are exposed to a gaseous mixture of CO + O2. The rapid agglomeration of Pd atoms under CO oxidation conditions even at 6 °C leads to the presence of Pd particles along with single atoms during CO oxidation experiments. Thus, the observed CO oxidation has contributions from both single Pd atoms and Pd particles.